Social Housing qualitative aspects - Fiscarelli, Dr. Arq. Diego Martín (Universidad Nacional del Litoral, 2018)
The family life cycle entails shifting and changes in size, structure and needs in relatively short and dynamic periods. To the contrary, public housing aimed at low-income citizens and stemming from Construction Programmes like turnkey models are developed taking into consideration stable and universal models for accommodation in limited spaces. The end product of these projects, generally located in urban and peripheral territories, reveals their quality and effectiveness when unforeseen home additions are needed; the family habitat transformation is the norm rather than the exception. Housing tends to call for men decisive intervention, and that environmental appropriation and transformation reflect the building processes of particular ways of inhabiting a space. These have major influences, such as rapid technological advances and global changes. Also, and probably most importantly, building processes are sensitive to inhabitants’ state of affairs and their particular demands for space setting. Tending to these matters, consider planning as a vital tool for disciplinal knowledge, and selecting Investigación Proyectual as the most suitable epistemic framework, this thesis aims at identifying the aspects involved in the notion of adaptability, especially its strategies and project resources. Delimiting the subject within the minimum standards of quality for public housing, these concepts will allow to verify the interrelation between adaptability and the local planning production developed after the implementation of the Sub-programme of Urbanization of Slums and Precarious Settlements (2005). Even though the main focus was on the interrelation suggested in the Sub-programme of Urbanization of Slums and Precarious Settlements within federal policies, the aim of this article is to offer the possibility ofof reviewing some of the current construction planning normative. These norms prevent consideration of adaptability as constitutive of the minimum standards of quality as well as of the parameters used to define the contemporary housing. Ultimately, these norms describe a long-standing and particular way of considering public housing developments aimed at low-income customers.